IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH MENENGAH KEJURUAN - Firdaus, Rizky; Sahrudin, Sahrudin; Bahrudin, Nugi; Firmansyah, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The success of Islamic Religious Education (PAI) learning depends not only on the creativity of teachers in the classroom, but also on the extent to which the principal's management is able to organize resources, provide infrastructure that supports a religious atmosphere, and conduct ongoing supervision. Without effective management implementation from the principal—whether as a manager, supervisor, or motivator—Islamic Religious Education (PAI) learning in vocational schools risks becoming trapped in mere administrative fulfillment without addressing the substantive aspects of character building. This qualitative research, using a case study at SMK PGRI 15 Jakarta, aims to analyze the principal's strategies for improving the quality of Islamic Religious Education (PAI) learning within the vocational school. The results indicate that improving the quality of PAI is achieved through four key management functions: planning integrated into the School Operational Curriculum (KOS), organization through the formation of a religious development team, and implementation, which includes academic supervision, the use of digital technology, and the implementation of a hidden curriculum through the promotion of religious practices. Furthermore, monitoring and evaluation are conducted periodically to maintain the relevance of learning methods. This study concludes that the principal's multifunctional role as educator, manager, administrator, supervisor, and motivator (EMAS-M) is key to creating an adaptive PAI learning ecosystem capable of shaping students' religious character amidst the demands of vocational competencies.